Studi Literature: Pengaruh Kemampuan Auditor, Skeptisme Profesional Auditor, Dan Teknik Audit Terhadap Efektivitas Pelaksanaan Audit Investigasi Dalam Pengungkapan Kecurangan - Irma Retno Dewi; Tri Ratnawati (International Forum of Researchers and Lecturers, 2024)
The purpose of this research is to determine the ability of auditors, professional skepticism of auditors, and audit techniques on the effectiveness of carrying out investigative audits in disclosing fraud. This research uses a description based on a literature review of previous research regarding the Influence of Auditor Ability, Auditor Professional Skepticism, and Audit Techniques on the Effectiveness of Carrying Out Investigative Audits in Disclosure of Fraud. The technique used in this research is collecting, comparing and analyzing previous research related to the role of auditors in preventing and detecting fraud. The results of this research show that the auditor's ability, the auditor's professional skepticism and audit techniques have a positive effect on the effectiveness of carrying out investigative audits in disclosing fraud so that the higher an auditor's ability, the smaller the error rate and the more effective the implementation in disclosing fraud.